Numerical Estimation of Mixed Convection Heat Transfer of Nannofluids Flowing In Horizontal and an Inclined Concentric Annuli - Faisal Sultan, Khalid (Journal of Engineering and Sustainable Development, 2013)
A theoretical study has been conducted on a fully developed laminar flow of a nanofluid under the action of mixed convection heat transfer. The nanofluid flows in a horizontal and inclined annulus. The outer cylinder of the annulus is kept adiabatic while the inner cylinder is studied in two cases: Constant Wall Temperature (CWT) and Uniform Heat Flux (UHF). The energy equation was first solved using Alternating Direction Implicit (ADI) method. Then, the momentum and continuity equations were combined to obtain a pressure correction formula. The numerical procedure has implemented a computer via Fortran power station software. The numerical results for the two boundary conditions considered are given in terms of stream function contours and isotherms for values of Rayleigh number Ra of 103,105 and106 and volume fractions Φ of 0.5%, 2%, and 4%. The effects of nanofluid type and particle size are considered in this study. Results showed that the secondary flow created by the natural convection has a significant effect on the heat transfer process. The Nusselt number estimated was higher in the UHF case than that of the CWT case for the same values of Reynolds number (Re), Rayleigh number, and volume fraction. Nan particles concentration did not reveal a serious effect on the secondary flow, axial flow profile, and the average skin friction coefficient. While increasing volume fraction and Rayleigh number significantly increase Nusselt number.